2014
DOI: 10.1016/j.jcis.2014.02.030
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption mechanisms of thallium(I) and thallium(III) by titanate nanotubes: Ion-exchange and co-precipitation

Abstract: Hydrothermally-synthesized titanate nanotubes (TNTs) are found to be excellent at adsorption of highly toxic thallium ions. Uptake of both thallium ions is very fast in the first 10 min. The adsorption isotherm of Tl(I) follows the Langmuir model with maximum adsorption capacity of 709.2 mg g(-1). Ion-exchange between Tl(+) and Na(+) in the interlayers of TNTs is the primary mechanism for Tl(I) adsorption. Excess Tl(+) undergoes further exchange with H(+). The adsorption mechanism is different for Tl(III), and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 108 publications
(34 citation statements)
references
References 49 publications
0
34
0
Order By: Relevance
“…It was because TNFs were positively charged in these pH ranges, thus capture of Hg(II) cations was inhibited due to electrostatic repulsion. 45 When pH was increased to 4, the adsorption capacity sharply increased to 224.6 mg g À1 because the surface charge of TNFs turned negative (Fig.…”
Section: Adsorption Of Hg(ii) By Tnfsmentioning
confidence: 99%
See 1 more Smart Citation
“…It was because TNFs were positively charged in these pH ranges, thus capture of Hg(II) cations was inhibited due to electrostatic repulsion. 45 When pH was increased to 4, the adsorption capacity sharply increased to 224.6 mg g À1 because the surface charge of TNFs turned negative (Fig.…”
Section: Adsorption Of Hg(ii) By Tnfsmentioning
confidence: 99%
“…Aer hydrothermal treatment for synthesis of TNFs, all the anatase transformed into titanate. 12,45 Furthermore, no crystalline Hg(II) or relegated compounds formed aer adsorption, indicating that ion-exchange just processed in the interlayers. 31-1329).…”
Section: Selective Adsorption Of Hg(ii) In the Presence Of Coexistingmentioning
confidence: 99%
“…Pore diameter (nm) phase [17,25]. The temperature for phase transformation is dependent on the morphology of TNTs, addition of additives and synthesis temperature and duration of TNTs [25,32].…”
Section: As-synthesized Tntsmentioning
confidence: 99%
“…Doong). removal of heavy metal ions, radioactive elements and rare earth elements such as Cs(I), Cd(II), Pb(II), Cu(II), Tl(II), and Eu(III) [17][18][19]. A previous study has reported that the adsorption capacity of metal ions onto hydrothermally as-prepared TNTs followed the sequence Pb(II) Cd(II) > Cu(II) > Cr(III), and the adsorption capacity was up to 2.64 mmol/g for Pb(II) and 1.92 mmol/g for Cu(II) [20].…”
Section: Introductionmentioning
confidence: 99%
“…Tl exists as Tl(I) and Tl(III) in the environment, and the former form has relatively high solubility and forms only weak complexes so that Tl(I) is readily transported through aqueous routes into the environment. Industrial wastewater, solid waste from coal combustion, and metal smelting are the main anthropogenic sources of Tl . The fascinating chemistry and high toxicity potential make Tl and its compounds of particular scientific interest and environmental concern.…”
Section: Introductionmentioning
confidence: 99%